A CD30(−) Transformed Mycosis Fungoides Case Responding Very Well to Systemic Bexarotene and Methotrexate. (June 2014) - Zindanci, Ilkin; Kavala, Mukaddes; Turkoğlu, Zafer; Can, Burce; Ozturk, Erman; Zemheri, Ebru; Akbulak, Ozge; Mansuroglu, Cem; Topaloğlu Demir, Filiz
The course of mycosis fungoides (MF) is indolent except when transformation to a large T-cell lymphoma occurs. The diagnosis of transformed MF relies on the presence of more than 25% of large cells on biopsy of an MF lesion. Treatment of transformed MF is a major challenge as these patients have poor outcome. Here, we report a 61-year-old man presenting with tumoral ulcer on the plantar area of the foot who was diagnosed cutaneous CD30(−) large cell transformed MF and treated with systemic methotraxate and bexarotene therapy.